2023
DOI: 10.1108/pr-06-2023-0511
|View full text |Cite
|
Sign up to set email alerts
|

Defender, Disturber or Driver? The ideal-typical professional identities of HR practitioners

Lisa Ferm,
Andreas Wallo,
Cathrine Reineholm
et al.

Abstract: PurposeThis study aims to contribute knowledge about different professional identities represented among HR practitioners from Weber's “ideal types” framework.Design/methodology/approachThe paper is based on semi-structured interviews with 34 Swedish HR practitioners working in large public and private organisations.FindingsThe findings reveal that HR practitioners' identity is perceived as indistinct, unclear and shattered, which leaves lots of room for interpreting HR identity. Based on a thematic content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…They confirmed that HR professionals need efficient analytical and other problem-solving skills to be effective business partners. The specific roles of HR professionals in businesses were examined by Ferm et al (2023) who interviewed 34 HR professionals from large private and public organizations in Sweden. The most common roles of interviewed HR professionals were related to the support of activities of line managers, the promotion of interests of employees, and the enhancement of organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They confirmed that HR professionals need efficient analytical and other problem-solving skills to be effective business partners. The specific roles of HR professionals in businesses were examined by Ferm et al (2023) who interviewed 34 HR professionals from large private and public organizations in Sweden. The most common roles of interviewed HR professionals were related to the support of activities of line managers, the promotion of interests of employees, and the enhancement of organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…HR professionals organized in HR departments usually operate in medium and large businesses employing hundreds and thousands of employees (Nguyen et al, 2019). In such businesses, HR professionals are involved in such HR activities as planning, recruiting, hiring, onboarding, rewarding, training, and offboarding (Ferm et al, 2023). HR professionals ensure these HR activities mainly administratively and methodically while cooperating with line managers responsible for their day-to-day performance (Bainbridge, 2015).…”
Section: Introductionmentioning
confidence: 99%